Habilidade de leitura e escrita em crianças disléxicas e leitores competentes - Uma análise de grupos contrastantes na bateria de leitura e escrita computadorizada (BALE-Computadorizada) - Piza, Carolina Mattar Julien de Toledo [UNIFESP] (2009)
The analysis of undergoing cognitive processes in reading and writing skills can help us distinguish different profiles of reading abilities. The present study aims to compare the performance of dyslexic children with two individually matched control groups (one contrasting in reading competence, but not age and a second contrasting in age, but not in reading competence) in a Brazilian Reading and Writing Battery. Participants were: 28 dyslexics of both genders, with mean age of 9,82 (±1,44) years, studying in public and private schools. These were matched to: 1) an Age Control Group (AC): composed of 26 good readers, with mean age of 9,77 (±1,44) years, matched by age, sex, years of schooling and type of school. 2) Reading Control Group (RC): composed of 28 younger controls, with a mean age of 7,82 (±1,06) years, matched by sex, type of school and reading level. All groups were tested on 4 tasks of the battery entitled “BALE”. These were: 1. Sentence Reading Comprehension Test (SRCT), 2. Sentence Hearing Comprehension Test (SHCT), 3.Picture-Print Writing Test (PPWT 1.1-Writing) and 4. Word Reading Competence Test (WRCT). Such tasks evaluate sentence reading comprehension, oral sentence comprehension, spelling and reading of isolated words and pseudowords. Results showed dyslexics obtained lower total scores and a higher execution time, when compared AC. When compared to RC, no differences in total scores of reading tasks or oral comprehension tasks were observed. However, dyslexics presented a slower reading speed, with a higher execution time and a lower score in spelling tasks, even when compared to younger controls. Detailed analysis of types of errors on word and pseudoword reading, demonstrated that dyslexics obtained lower scores in the reading of pseudowords, when compared to both groups. Such findings suggest that overall scores of dyslexics were similar to the younger readers. However, specific deficits in phonological and visual decoding, showed both groups have different underpinning reading strategies.